Nestedness of hoopoes' bacterial communities: symbionts from the uropygial gland to the eggshell. (18th February 2016) - Soler, Juan J.; Martínez‐García, Ángela; Rodríguez‐Ruano, Sonia M.; Martínez‐Bueno, Manuel; Martín‐Platero, Antonio M.; Peralta‐Sánchez, Juan M.; Martín‐Vivaldi, Manuel
Abstract : How microbial symbionts are established and maintain on their hosts is a leading question with important consequences for the understanding of the evolution and functioning of mutualistic relationships. The acquisition by hosts of mutualistic microbial symbionts can be considered as colonization processes of environments (i.e., host) by symbionts. Colonization processes can be explored by characterizing the nestedness of communities, but this approach has rarely been applied to communities of microbial symbionts. We used this approach here, and estimated the nestedness of bacterial communities of hoopoes ( Upupa epops ), a species with symbiotic bacteria in their uropygial gland that are expected to colonize eggshells where they protect embryos from pathogens. Bacterial communities were characterized by ARISA (Automated rRNA Intergenetic Spacer Region) and studied the nestedness characteristics of bacterial communities living in the uropygial secretion, bill, belly and eggshells of each sampled female hoopoes. We detected a consistent nested pattern of bacterial communities of hoopoes; from the uropygial gland to the eggshell. We also found evidence of study year and reproductive events influencing the level of nestedness of bacterial communities of hoopoes. These results indicate that bacterial communities of eggshells and body parts of female hoopoes are at least partially conditioned by the symbiotic community in the uropygial gland. We discuss the importance of these results for understanding this host–microbial mutualism functioning and evolution.